1969
DOI: 10.1002/cpt1969103292
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives in adrenergic beta‐receptor blockade

Abstract: The adrenergic {3-receptor blocking drugs currently undergoing clinical evaluation are classified in relation to their pharmacological properties. Particular consideration is given to those pharmacological properties that may be of importance in the clinical application of these drugs. The present evidence on the role in the {3-blocking action of propranolol in angina pectoris and arrhythmias is reviewed, and it is concluded that this property is of major significance in these indications. Finally, recent adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
1

Year Published

1969
1969
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(50 citation statements)
references
References 9 publications
0
49
1
Order By: Relevance
“…Propranolol, in addition to blocking 13-receptors, is equipotent to lidocaine as a local anaesthetic on cardiac muscle strips (Morales-Aquilera & Vaughan Williams, 1965). The plasma concentration required for this activity (greater than 10 ig/ml) is 100 times that required for P-receptor blockade (Fitzgerald, 1969). However, Veldhuis et al (1980) have demonstrated that timolol, a non-membrane active Pantagonist (Conolly, Kersting & Dollery, 1976) inhibits adrenaline-stimulated ODC induction in granulosa cells of the pig in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Propranolol, in addition to blocking 13-receptors, is equipotent to lidocaine as a local anaesthetic on cardiac muscle strips (Morales-Aquilera & Vaughan Williams, 1965). The plasma concentration required for this activity (greater than 10 ig/ml) is 100 times that required for P-receptor blockade (Fitzgerald, 1969). However, Veldhuis et al (1980) have demonstrated that timolol, a non-membrane active Pantagonist (Conolly, Kersting & Dollery, 1976) inhibits adrenaline-stimulated ODC induction in granulosa cells of the pig in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…One of the main uses of 8-adrenoceptor blocking drugs is in the treatment of angina pectoris and the clinical value of propranolol in this condition has been especially well documented (see Fitzgerald, 1969). It is a valuable drug, acting by reducing the oxygen needs of the myocardium and perhaps also by antagonizing the myocardial calorigenic (or " oxygen wasting ") effects of released catecholamines (Shanks, 1967;Parratt, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…The ability to block ,B-adrenoceptors in cardiac muscle has been considered to be the basis of their therapeutic effect (Fitzgerald, 1969). Some of these drugs, notably propranolol, frequently induce respiratory distress in asthmatic subjects, an effect thought to result from block of ,¢adrenoceptors in airways smooth muscle (McNeill, 1964;Richardson & Sterling, 1969 practolol .…”
mentioning
confidence: 99%